Immunization of goats against brucellosis (summary of the experiments concerning the isolation, properties and behavior of a type of vaccine) - Elberg, Sanford S. (1959)
The search for untipo of brucellosis melitensis could be used as immunizing agent began with studies Montpellier group, whose work led to the implementation of a living type combined with both the Bolvin type of antigen derived from a virulent type (Lisboa, Roman, Renoux, 1939), when anacultures with virulent type (Carrere and Quatrefages, 1951).